"The queen stays queen, adios" the impact of editing on the legacies of women winners of color on Survivor (2000-2022) - Vesliño, Matthew Lorenzo Dimagiba; Ilagan, Cecile Angela A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study interrogates the narrative faculties of editing for reality television, in particular its capacity to reflect various realities through results-oriented storytelling. Specifically, this critiques the editing of the competitive reality television series, Survivor (2000–) and how the editing of its women winners of color impact the stories of their respective successes. In order to develop a more comprehensive understanding of how editing for competitive reality television is intentional in its weaving of narratives for successful individuals with marginalized identities, this study employs the fan-made, formalist framework of Edgic as explored by Holmes (2015) and Lindbergh (2020), while grounded by Crenshaw's (1991) lens of representational intersectionality to understand the ways in which intersectional hegemony pervaded their media representations on Survivor. This study finds that the editing logic of Survivor ultimately underrepresented, undervalued, and undersold the legacies of these women winners of color as subordinate to their white and/or male competitors, even when their multidimensional stories were far more nuanced than their edited portrayals had made them seem.

KEYWORDS: Formalist criticism, representational intersectionality, identity, media representation, representation in media, editing, television, competitive reality television critical analysis, textual analysis
Sa pagsusuring ito, iniiimbestigahan at pinupuna ang mga epekto ng pag-edit ng Amerikanong programing Survivor (2000—) upang tumatak sa alaala ang mga kuwento ng kababaihang may kulay na nanalo rito. Upang mapatunayang sadyang na-edit ang salaysay ng mga nanalong kababaihan sa mga paraang hindi makatwiran ayon sa kanilang pagkakakilanlan bilang mga babaeng may kulay, marling ginagamit ng sanaysay na ito ang Edgic nina Holmes (2015) at Lindbergh (2020). Isang teorya na umusbong sa mismong komunidad ng mga taga-hanga ng Survivor, at bilang na rin sa pagsusuri nito ang representational intersectionality ni Crenshaw (1991). Sa panonood ng mga napiling season ng Survivor, natuklasan ng pag-aaral na ito na maselan ang pag-edit ng programa sa mga kababaihang may kulay na nanalo rito. Mas binibigyang halaga ang mga perspektibo ng kanilang mga mapuputi at/o lalaking katimpalak, kahit natatangi at makabuluhan din ang mga kuwentong ukol sa pagkakakiklanlan ng mga nanalong kababaihang may kulay.

MGA KEYWORD: Formalist criticism, representational intersectionality, identity, media representation. representation in media, editing, television, competitive reality television, critical analysis, textual analysis
Vita.
Undergraduate thesis
Includes bibliographical references (pages 142-146) and appendices (pages 147-474).
Keywords: Reality television program; Women in mass media .